The Results of Different Heating Temperatures on Activities of Bioactive Proteins in Human Milk. (May 2023) - Zhang, Jie; Duley, John A.; Cowley, David M.; Shaw, Paul N.; Zhou, Peng; Koorts, Pieter; Bansal, Nidhi
Background: The most utilized pasteurization method in donor human milk banks is Holder pasteurization (heating 62.5 °C for 30 min). However, many bioactive proteins are heat sensitive and are inactivated. Research Aim: To determine the results of a range of heating regimes on the activities of xanthine oxidase, lactoperoxidase and lysozyme, the concentrations of immunoglobulin A and lactoferrin, as well as bacterial inactivation. Method: This prospective, cross-sectional, intervention study was designed to measure the influence of heating temperatures on bioactive components in donor human milk. Milk samples were processed at 40, 50, 55, 62.5, 75, 127 °C and the activities of the enzymes, and the concentration of immune proteins, were measured. Results: No bacterial colonies were detectable, using standard culture methods, after heating above 50 ºC. All proteins studied retained over 60% concentrations or activities when the pasteurization temperature was 50 ºC or lower, while their concentrations or activities were lost at higher temperatures. For lactoferrin, the residual concentration was above 80% when heating temperature was under 55 °C, while only 20% remained after Holder pasteurization. Both xanthine oxidase and lactoperoxidase had little residual activity when temperatures were above Holder pasteurization. Lysozyme retained a greater proportion of residual activity than other proteins, following heating at all temperatures. Conclusions: The concentrations or activities of immune proteins and bioactive enzymes decreased when heated above 50 °C. The results of this study can be used to design temperature control guidance during alternative methods of pasteurization.